Analisis Preferensi Konsumen Terhadap Minuman Kopi Arabika Dengan Menggunakan Metode Analisis Conjoint - Delafrisila, Amanda; Hernosa, Siswa Panjang (Universitas Galuh, 2025)
The purpose of this study was to examine the quality valued by customers in Arabica coffee drinks, including gender, age, education, occupation, and income, in thirty-nine coffee shops. In addition, this study will examine the attributes of the order of Arabica drinks and the quality and level preferred by customers. Conjoint analysis, validity analysis, and reality analysis are some of the information analysis techniques. The findings show that: Cronbach's Alpha 0, 50–0, and 70 1 indicate that all statements are reliable, and the validity test in the variation of characteristics, price, and means shows that all statements are valid based on sig values less than 0.05. Arabica coffee is more likely to be purchased by respondents. Age 18–28 is the largest group, consisting of 58 people. Respondents with the highest high school education are the largest consumers, consisting of about 45 people. Respondents from thirty-nine coffee shops have various work styles, and a large number of them are consumers, with about thirty-six of them being private workers. 2. Characteristics of Arabica coffee that are attractive to consumers. consists of the following: Smoking area facilities, espresso variations, price of Rp 12,000, and finally. fast service with a smile and greeting. 3. Aspects of Arabica coffee that are important to consumers Facilities, Variants, Prices, and services are components of Arabica coffee drinks.